2013
DOI: 10.1681/asn.2012030268
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ-Lyase Protects against Renal Ischemia/Reperfusion by Modulating Oxidative Stress

Abstract: Hydrogen sulfide (H 2 S) is an endogenous gasotransmitter with physiologic functions similar to nitric oxide and carbon monoxide. Exogenous treatment with H 2 S can induce a reversible hypometabolic state, which can protect organs from ischemia/reperfusion injury, but whether cystathionine g-lyase (CSE), which produces endogenous H 2 S, has similar protective effects is unknown. Here, human renal tissue revealed abundant expression of CSE, localized to glomeruli and the tubulointerstitium. Compared with wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
147
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 40 publications
15
147
3
Order By: Relevance
“…Previously, it was demonstrated that CSE deficiency is linked to increased levels of oxidative stress (42). As a readout for oxidative stress, we used OxyBlot analysis as previously described (43).…”
Section: Overexpression Of Cse Reduces Levels Of Oxidative Damage Of mentioning
confidence: 99%
“…Previously, it was demonstrated that CSE deficiency is linked to increased levels of oxidative stress (42). As a readout for oxidative stress, we used OxyBlot analysis as previously described (43).…”
Section: Overexpression Of Cse Reduces Levels Of Oxidative Damage Of mentioning
confidence: 99%
“…[28][29][30][31] The proangiogenic effect of H 2 S was first described by Cai et al, who showed that an exogenously administrated H 2 S donor (sodium hydrosulfide [NaHS]) promoted proliferation, migration, and tube-like structure formation in endothelial cells in vitro. 32 In vivo, it was demonstrated that H 2 S is a proangiogenic factor in a model of hind limb ischemia.…”
mentioning
confidence: 99%
“…H 2 S protects the luminal surface of blood vessel from oxidative stress caused by ischemia/reperfusion injury, as well as from development of atherosclerotic lesions, [28,122].…”
Section: The Roles Of H 2 S and No In Oxidative Stressmentioning
confidence: 99%
“…Moreover, CSE overexpression reduces the amount of reactive oxygen species (ROS) produced during stress in renal tissues [122]. NaHS has been shown to mitigate the methionine-induced production of free radicals in brain ECs (bEnd3) and to enhance the inhibitory action of reduced glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) and L-NAME on ROS production [123].…”
Section: The Roles Of H 2 S and No In Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation